2015
DOI: 10.1111/iju.13003
|View full text |Cite
|
Sign up to set email alerts
|

Salvage autologous fascial sling after failed synthetic midurethral sling: Greater than 3‐year outcomes

Abstract: Objective: To determine long-term surgical outcomes of salvage autologous fascial sling placement after a failed synthetic midurethral sling. Methods: Women who had undergone autologous fascial sling placement without concomitant pelvic surgery for a failed synthetic midurethral sling utilizing mesh with a minimum follow up of 36 months were identified. Charts were reviewed, and patients were contacted by telephone. Success was determined by the Patient Global Impression of Improvement. Secondary measures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…At 74 months of followup, 52% of patients remained dry. 15 It is our opinion that patients with a mild to moderate degree of leakage benefit from repeat RPR MUS, and those with more severe leakage are more likely to benefit from PVS (Fig. 1).…”
Section: Surgical Interventionmentioning
confidence: 95%
“…At 74 months of followup, 52% of patients remained dry. 15 It is our opinion that patients with a mild to moderate degree of leakage benefit from repeat RPR MUS, and those with more severe leakage are more likely to benefit from PVS (Fig. 1).…”
Section: Surgical Interventionmentioning
confidence: 95%
“…Mesh excision did not relate to worse outcomes (p=0.013) [50]. Another retrospective study of 21 patients who performed PVS after failed A c c e p t e d A r t i c l e MUS resulted in no statistical impact on whether concomitant sling excision (n=8) or not (n=13) (p=0.62) [51]. However, it seems reasonable to remove the first sling if repeat surgery is necessary due to the complications related to mesh exposure, pain, and postoperative voiding difficulty.…”
Section: Concurrent Excision or Removal Of The Prior Slingmentioning
confidence: 97%
“…The cure rates of PVS using autologous fascia as second-line management have been reported to be 60-80% [49][50][51][52][53]. A retrospective study of 66 patients (16 pure SUI vs. 50 mixed incontinence) who got an autologous PVS after failed MUS reported that 69.7% of the cure of SUI.…”
Section: Pubovaginal Sling With Autologous Rectus Fasciamentioning
confidence: 99%
See 1 more Smart Citation
“…75 The use of autologous fascial slings for recurrent SUI have reported success rates of 52% to 91%. 76,77 They are more appropriate for women with severe leakage or ISD as they can be tensioned to increase urethral resistance (as opposed to s-MUS, which must be inserted tension free) and for those who have failed more than one tape. 61 AUS insertion in women is indicated for patients with severe SUI due to ISD.…”
Section: Case Iib: Mesh Complication Following Insertion Of Tvt-omentioning
confidence: 99%